Halitosis: Classification, causes, and diagnostic as well as treatment approach – A Review - Mahadeva Rao, U.S; Suganya, M. Utharkar; C. Shanmuga, Sundaram (2015)
Objectives: This coverage reviews the current knowledge on classification, causes, and diagnostic as well as remedial line of attack on malodor of breath. Data: Halitosis, a condition that causes a severe social handicap to those who suffer from it, has a multifactorial etiology. It is anasty or offensive odor originating from the breath. The condition may encompass both oral and non-oral disorders. Sources: A private, monthly with keywords halitosis, malodor, etiology, measurement, and management from Medline and Pub med updated database of literature was reviewed. Conclusions: In majority of cases, halitosis is caused by oral conditions, defined as oral malodor. Oral malodor fallouts from tongue coating, periodontal disease, peri-implant disease, deep carious lesions, exposed necrotic tooth pulps, pericoronitis, mucosal ulcerations, healing (mucosal) wounds, impacted food or debris, imperfect dental restorations, unclean dentures, and factors causing decreased salivary flow rate. The basic progression is microbial degradation of organic substrates. Non-oral etiologies of halitosis include turbulences of the upper and lower respiratory tract, ailments of the gastrointestinal tract, some systemic maladies, metabolic disorders, medications, and carcinomas. Stressful situations are predisposing factors. There are three primary measurement approaches of halitosis. Organoleptic measurement and gas chromatography are very dependable, but not very simply clinically applied techniques. The use of organoleptic measurement is recommended as the ‘gold standard’. Gas chromatography is the preferable method if accurate measurements of specific gases are required. Sulphide monitoring is straightforwardly used method, but has the limitation that important odors are not detected. The scientific and practical value of additional or alternative measurement methods, such as BANA test, chemical sensors, salivary incubation test, quantifying β-galactosidase activity, ammonia monitoring, ninhydrin method, and polymerase chain reaction, has to be established. Last but not least, regarding the usage of probiotics, the oral administration of the probiotic lactobacilli not only seemed to improve the physiologic halitosis, but also showed beneficial effects on bleeding on probing from the periodontal pockets.